Negative Cultural Impacts Due To Tourism Development-A Comparative Study between Urban and Rural Tourist Centres of Kerala: Comparing Negative Cultural Impacts of Tourism Development in Urban and Rural Tourist Centres of Kerala (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The study is conducted by selecting a sample of four hundred respondents from urban and rural tourist centres of Kerala in order to compare the influence of negative cultural factors among those two. One hundred and fifty one respondents are selected from urban centres and two hundred and and forty nine from rural centres. The main objective of the study is to find out which centre is worst affected by negative cultural impacts due to the development of tourism. It is found out from the study that in all the six variables indicating the negative cultural impact, the urban centres of Kerala are leading with the highest Mean Scores. Hence urban centres are popularly affected by those factors than rural.